Analysis of The Physical Condition of Jambi Province Sepak Takraw Athletes Heading Into the 2024 Aceh-North Sumatra PON - Patima, Patima; Munar, Hendri; Hasibuan, Mhd Usni Zamzami (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research aims to determine the physical condition of sepak takraw athletes in Jambi Province. From the test results, the physical condition of these components will be linked to the achievements of athletes who have won national level championships. Components of physical condition that will be examined include: strength, agility, endurance, leg muscle explosive power, abdominal muscle strength, back muscle strength. This research is associative quantitative research. The samples or research locations were sepak takraw athletes from Jambi province who took part in the 2024 Aceh-North Sumatra PON championship with a total of 5 athletes. Data collection uses tests and measurements, with the following instruments used, 1. Strength 2. Endurance 3. Speed ​​4. Flexibility 5. Explosive power 6. Agility 7. Coordination 8. Balance 9. Accuracy 10. Reaction. The following is the average value and category of physical condition for each test item. The average endurance obtained was 38.8, which is in the good category, the leg muscle explosive power test of 40 cm which was measured using the Vertical Jump test was included in the fair category, the agility test was 15.75 seconds, which was measured using the 40 meter Shuttlerun test was included in the very good category, the strength test of 35 times which was measured using the 1 minute push up test was included in the good category, the muscle strength test. stomach 80 times, as measured using the 1 minute Sit Up test, is included in the very good category. From the results of the ranking of physical conditions and achievements that have been obtained, it can be concluded that there is a significant relationship between an athlete's physical condition and the achievements they achieve theoretically. However, in the statistical data analysis of the correlation test, there was no relationship between physical condition and athlete performance because the sample that influenced the data was not significant.